God's Agents : Biblical Publicity in Contemporary England. - Engelke, Matthew, 1972- (Anthropology of Christianity ;, 2013)
The British and Foreign Bible Society is one of the most illustrious Christian charities in the United Kingdom. Founded by evangelicals in the early nineteenth century and inspired by developments in printing technology, its goal has always been to make Bibles universally available. Over the past several decades, though, Bible Society has faced a radically different world, especially in its work in England. Where the Society once had a grateful and engaged reading public, it now faces apathy-even antipathy-for its cause. These days, it seems, no one in England wants a Bible, and no one wants o.